If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + 2 = 1 Reorder the terms: 2 + -2a = 1 Solving 2 + -2a = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2a = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -2a = 1 + -2 -2a = 1 + -2 Combine like terms: 1 + -2 = -1 -2a = -1 Divide each side by '-2'. a = 0.5 Simplifying a = 0.5
| 6-8x=15-36x | | 6-8x=15-6x | | x^2-11x+25=3x+1 | | 6=5x-5 | | 3-y=-31 | | 7-2x=x | | x^2-4x-17=4 | | -4d=5d-17 | | 2x+15-x=14 | | 17a+17b= | | 130.74=179.4*n | | 3X+6=43+X | | 130.6=283.2*n | | 15-6t=-11t | | -11/4x=7 | | 2x+5=7x-4 | | 3w^2+8w+5= | | 13*x^2-8=5 | | (3+5x)(3-5x)= | | 9+3n=(4+5)3-6 | | y=ln(x^2-9) | | 12+8m=100 | | 13*x^2-11=3 | | h/6-29=-21 | | y=(x-5)/(x+5) | | (25+35x)/15=4 | | (3x^2)-(44x)+120=0 | | 8-s=4t+3 | | f(x)=x^2-9 | | .25q=3w+3 | | p/3+3= 5 | | 6n+2=50 |